Design and characterization of biodegradable thermoplastic elastomers - Kong, Jen Fong. (2013)
In this thesis, biodegradable thermoplastic elastomers were developed through the structural design of copolymers based on caprolactone and lactide. The copolymers comprised of 2 segments, namely an amorphous middle block, made up of caprolactone and L-lactide, and crystallizable end blocks, made up of mainly poly(L-lactide).